University Enrolment in Canada 1951-83 and Beyond - Vanderkamp, John (Canadian Journal of Higher Education, 1984)
Canadian university enrolment has increased dramatically over the last three decades. This paper discusses the time pattern of university participation rates and the variations across provinces in the light of economic analysis. A number of potentially important factors are examined. While cost factors, tuition fees and student aid, have changed significantly, it. is argued that their quantitative impact is unlikely to account for a major part of the enrolment increase. Because university enrolment leads to additions to the stock of educated labour the paper analyzes the relations between stocks and flows. It is concluded that continuing participation rates at recent levels are only compatible with fairly rapid growth in the stock demand for highly educated labour over the next half century. The rise in community colleges since the late sixties presents a complicated factor, in part because in some provinces these colleges provide university transfer programs. It is likely that the slow-down in university participation rates during the seventies is at least in part attributable to the growth of the college system as a 'competitive' alternative. It is also argued that the increase in the size of the youth cohort contributed to this slow-down. Despite the conventional wisdom, the impact of unemployment on university enrolment rates is not easy to detect.